2017
DOI: 10.1080/15438627.2017.1314292
|View full text |Cite
|
Sign up to set email alerts
|

The impact of patellar tendinopathy on sports and work performance in active athletes

Abstract: Greater insight into sports and work performance of athletes with patellar tendinopathy (PT) will help establish the severity of this common overuse injury. Primary aim of this study is to investigate the impact of PT on sports and work performance. Seventy seven active athletes with PT (50 males; age 28.1 ± 8.2 years; Victorian Institute of Sports Assessment Patella 56.4 ± 12.3) participated in this survey. Sports performance, work ability and work productivity were assessed using the Oslo Sports Trauma Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 25 publications
0
37
1
2
Order By: Relevance
“…Using the OSTRC questionnaire in participants diagnosed with patellar tendinopathy, de Vries et al demonstrated a greater severity of patellar tendinopathy (ie, higher OSTRC score) than is reported in the current study (mean [SD] = 45.1 [23.2] compared to 25.3[17.7]). This is likely due to differences in the populations studied.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Using the OSTRC questionnaire in participants diagnosed with patellar tendinopathy, de Vries et al demonstrated a greater severity of patellar tendinopathy (ie, higher OSTRC score) than is reported in the current study (mean [SD] = 45.1 [23.2] compared to 25.3[17.7]). This is likely due to differences in the populations studied.…”
Section: Discussioncontrasting
confidence: 45%
“…This is likely due to differences in the populations studied. de Vries et al included participants who were seeking treatment whereas the current study included a non‐treatment seeking sporting population. However, the mean OSTRC score in the current study is similar to that reported in other sporting populations for other injuries …”
Section: Discussionmentioning
confidence: 99%
“…Tendinopathy often impacts the patient’s daily life in multiple biopsychosocial ways such as employment, mental health and quality of life on both a personal and a professional level [6]. Tendinopathy has been related to reduced work ability and decreased work productivity, particularly for physically demanding work [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patellar tendinopathy rehabilitation is an encompassing management of the athlete with the fundamental focus on exercise (Van Ark et al 2016 ). However, with the possibility of enduring persistent symptoms, full recovery from this pathology is not always certain (De Vries et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%